Use of gyrase B, toxr, hemolysin, luciferase, and ornithine decarboxylase genes to evaluate the phylogenetic classification of ten Philippine vibrio sp. isolates implicated in shrimp disease - Ranoa, Diana Rose Evangelista (Quezon City College of Science, University of the Philippines, 2006)
Ten Philippine Vibrio isolates pathogenic to black tiger shrimp (Penaues monodon) were previously classified to belong to either Vibrio harveyi or Vibrio campbelli based on conventional tests. In this study, amplification, isolation, and partial sequence analysis of gyraseB (gyrB), toxR, and hemolysin genes were performed on ten Philippine Vibrio isolates confirm earlier identification and classification. Sequence data of the amplified gyrB gene fragment from five out of ten isolates. (PN-9801, PIZ-9824, BR-9807, BRW-9804, and CRWP-9805) revealed 97-99% sequence similarity with V. harveyi (NBRC 15634T), but are also 92-97% similar to V. campbelli (NBRC 15631T). The five remaining isolates BS-9904, SW-9702,PIZ-9806, CRW-9807, and NRW-9805 showed only 84-92% and 87-92% identity with V. campbelli (NBRC-15631T) and V. harveyi (NBRC 15634T), respectively, but had 96-99% sequence similarity with a strain of V. harveyi (Vib 391) isolated from Thailand. Thus, the gyrB data alone could not help in resolving species identity of these ten Philippine Vibro isolates. Sequence analysis of the toxR gene revealed 97-100% sequence similarity among Philippine Vibro isolates, indicating that they may belong to the same classification. The ten isolates exhibited significant toxR gene sequence variation with both the type strains V. harveyi and V. campbelli, with only 92-93% and 74-75% sequence similarity with Vibrio campbelli and Vibro harveyi, respectively. Analysis of the partial hemolysin gene sequences revealed 88-99% similarity among the ten isolates. The ten isolates however, exhibited only 92-97% and 79-85% hemolysin gene sequence similarity with Vibrio campbelli and Vibro haveyi, respectively. The Philippines Vibrio isolates therefore could be distinguished from the type strain V. harveyi and V.campbelli based on partial toxR and hemolysin gene sequences. Moreover, based on these two genes, the Philippine isolates ap[pear to be more closely related to V. campbelli than V. harveyi. The ten isolates were compared to a V. harveyi (Vib 391) strain from Thailand, and they were found to be 98-99%, similarin terms of the toxR gene and 93-98% based on the hemolysin gene. These findings point out to the need to use more molecular markers to accurately classify environmental Vibrio strains exhibiting characteristics similar to both V. harveyi and V. campbelli based on conventional biochemical tests.
Thesis (M.S. Molecular Biology and Biotechnology)--University of the Philippines Diliman
Keywords: Bacterial genetics; Shrimps -- Philippines; Toxic torts -- Philippines